(untitled) (Physical Education, Health and Social Sciences, 2026)
Soybean (Glycine max [L.] Merr.), the world’s leading grain legume with annual production exceeding 353 million tons, relies heavily on biological nitrogen fixation (BNF) to meet its high nitrogen demands (50–80% or more of total N), offering a sustainable alternative to inefficient synthetic fertilizers (30–60% utilization) that contribute to environmental degradation. This review synthesizes current knowledge on BNF efficiency, effectiveness, and specificity in soybean, emphasizing the role of rhizobial diversity primarily Bradyrhizobium japonicum, B. diazoefficiens, and Sinorhizobium fredii in nodule formation, nitrogenase activity, and symbiotic performance. Genetic factors, including host genes (GmNFR1, GmNFR5, GmNIN) and bacterial nodulation factors (Nod factors), govern specificity and efficiency, while environmental stressors (drought, salinity, acidity) and agronomic practices (inoculation, co-inoculation with PGPR/mycorrhizae) modulate outcomes. Advances in microbiome engineering, horizontal gene transfer of symbiosis islands, and selection for elite strains promise enhancements in BNF rates (up to 300 kg N/ha), reducing fertilizer dependency and emissions. The analysis highlights integrated strategies for optimizing soybean productivity in diverse agroecosystems, supporting global food security and sustainability.